Screening for differentially expressed genes between left- and right-sided colon carcinoma by microarray analysis - ZHU, HONG (D.A. Spandidos, 2013)
Left-sided colon carcinoma (LSCC) and right-sided colon carcinoma (RSCC) differ in their genetic susceptibilities to neoplastic transformation. The present study identified 11 genes that were differentially expressed in LSCC and RSCC by expression profiling with microarray analysis. Compared with RSCC, the human genes for L-lactate dehydrogenase B chain (LDHB), cyclin-dependent kinase 4 inhibitor D (CDKN2D), phosphatidylinositol-4-phosphate-3-kinase C2 domain-containing subunit α (PI3KC2α), protocadherin fat 1 (FAT; a human protein that closely resembles the Drosophila tumor suppressor, fat) and dual specificity protein phosphatase 2 (DUSP2) were upregulated in LSCC. By contrast, genes for ubiquitin D (UBD), casein kinase-1 binding protein (CK1BP), synaptotagmin-13 (SYT1), zinc finger protein 560 (ZNF560), pleckstrin homology domain-containing family B member 2 (PLEKHB2) and IgGFc-binding protein (FCGBP) were downregulated in LSCC compared with RSCC. A quantitative polymerase chain reaction (qPCR) analysis revealed that the mRNA levels of UBD and CK1BP in LSCC were significantly lower compared with those in RSCC (P=0.033 and P= 0.005, respectively), whereas the mRNA levels of LDHB and CDKN2D in LSCC were significantly higher compared with those in RSCC (P=0.008 and P=0.017, respectively). Western blot and immunohistochemical analyses demonstrated that the expression of CDKN2D in LSCC was significantly higher compared with that in RSCC, while the expression of UBD in LSCC was significantly lower compared with that in RSCC. The present study provides important insights into the understanding of the molecular genetic basis for the different biological behaviors observed between LSCC and RSCC. These insights may therefore serve as a basis for the identification of novel colon cancer markers and therapeutic targets.